EVALUATION OF EVIDENCE BASED NURSING PRACTICES ON INFECTION CONTROL IN INTENSIVE CARE UNIT. - Salunkhe, Dattatray R; Mohite, Vaishāli R; Raje, Vinayak; Shinde, Mahadeo B (International Journal of Psychosocial Rehabilitation, 2020)
Hospital acquired infections brings about higher morbidity, mortality, and extra expenses. It is very much perceived that the risk of transmission of pathogens while giving clinical care and the frequency of Hospital acquired infections can be kept low through proper institutionalized anticipation strategies. Study was aimed to evaluate at the evidence based nursing practices on infection control and to find association between socio-demographic variable and evidence based nursing practices on infection control . Methods: Type of study-quantitative, preexperimental Descriptive study design was used. study was conducted at Krishna hospital is a teaching university hospital which is accredited by NABH.50 staff were selected through purposive sampling technique The current study was approved by institutional ethics committee of Krishna institute of medical sciences deemed to be university. Results: Majority of samples 46% were within the age group of 26-30. With respect to gender 56% were female and 44% were male. Most of the staff was Unmarried that is 58%. Most of the samples 42% were having 1-3 years of Year of experience, Majority of samples 50% were working in Medical Intensive care unit. Hand washing practices related to before Patient Contact Majority of nurses 98% did hand washing. Before Aseptic Technique 98% nurses did hand washing. Body Fluid Exposure Risk 100% nurses did hand washing. After Patient Contact 88% of nurses done hand washing and After Contact with Patient Surrounding 90% of nurses did hand washing. Majority 100% nurses Stored Sterile Material Properly. 80% of nurse’s external Devices Handle Aseptically and 20% were not external Devices Handle Aseptically. 88% practices Date of Opening on Tubes, Bottles and 86% of nurses practices Autoclave of all trays. Majority of nurses 74% practices Disinfection of Non Critical Patient Equipment and 26% were not practices Disinfection of Non Critical Patient Equipment. Majority of nurses 74% practices Linen Sorting and Disinfection of Soiled Linen 26% were not practices Linen Sorting and Disinfection of Soiled Linen. Majority 84% practices Personal protective equipment and 16% of nurses were not practices Personal protective equipment. Conclusion: The study results reveal that the appropriate use of evidence based practice on infection control by the nursing professionals working in intensive care settings.